Determination of constitutive friction laws appropriate for simulation of cutting processes. (August 2022) - Schulze, V.; Bleicher, F.; Courbon, C.; Gerstenmeyer, M.; Meier, L.; Philipp, J.; Rech, J.; Schneider, J.; Segebade, E.; Steininger, A.; Wegener, K.
Abstract: The influence of friction on machining processes as a function of pressure, velocity and temperature is neither deeply understood nor sufficiently definable for Finite-Element-Method (FEM) simulations. Current simulations therefore often use constant values for the friction coefficients. In this work, friction coefficients for SAE 1045 are determined from different tribometers. An empirical model is subsequently fit to the data and used in different FEM-tools to simulate orthogonal cutting. Results are compared to corresponding experiments. A final evaluation of the model reveals the challenges due to the elasto-plastic contact and thus the derivation and utilisation of such a model.